Relasi Insan Pers dan Politik: Studi tentang Kandidasi Margiono pada Pemilihan Bupati Tulungagung Tahun 2018 - Fatchurika Kartika Sandra (Universitas Airlangga, 2023)
The press and politics have different patterns of relations, and involve certain actors in them. This study aims to find out and analyze the relationship between the press and politics from Margiono, former Chairman of the Indonesian Journalists Association (PWI) and the influence of this relationship on Margiono's candidacy process as a candidate for Regent of Tulungagung Regency in 2018. This research uses qualitative methods with interviews as primary data collection method with the theoretical framework of candidate selection Reuven Hazan and Gideon Rahat is used to analyze the candidacy process. This research found that Margiono's candidacy process was carried out exclusively and centralized so that personal affinity, leadership and persona of Margiono could become his capital in the candidacy process.